The question on origin of the universe and Big Bang - Adhikari, Krishna Raj (Himalayan Physics, 2011)
School of thought is the theory of creation (theism) and school of thought deals with the random chance of evolution (atheism) about the origin of the universe and origin of the life. In the race of proof of the hypothesis, the theism has no scientific evidence and reliable proof, on the other hand atheism based on the scientific observable evidence. The latest theory of origin of the universe by Big Bang is more believable and supported by some scientific evidence such as Doppler effect on light, Hubble observation and result of the expanding the universe and observation of the cosmic microwave background radiation(CMBR). Paper briefly discussing about the origin of the universe and the Bing Bang. Key words: Big bang; Doppler; Cosmic microwave background radiation(CMBR) The Himalayan Physics Department of Physics, PN Campus, Pokhara Nepal Physical Society, Western Regional Chapter Vol.2, No.2, May, 2011 Page: 67-70 Uploaded Date: 1 August, 2011